'Even the dead will not be safe': the long war over school English*. (3rd September 2018) - Hardcastle, John; Yandell, John
ABSTRACT: Over the past two decades in England, those intent on the transformation of schooling have sought to win support for their neoliberal project by emphasising the difference between, on the one hand, their vision of what education is, and what it is for, and, on the other, the practices and forms of education that preceded the era of standards-based reforms. Different strategies have been adopted to enforce this message: while New Labour was largely content to ignore the past, to treat it as irrelevant to the needs and possibilities of new times, prominent figures within more recent Conservative-led administrations have re-written the history of schooling, traducing the progressive traditions that their project is designed to eradicate. We attempt to sketch out a different version of this history, one that speaks back to such reductive misrepresentations (the 'discourses of derision', as Stephen Ball has called them). We focus particularly on developments within the teaching of English in London schools, on the challenges that confronted teachers in successive periods of rapid social change, how they responded to these conditions and the resources that enabled them to explore different curricular and pedagogic possibilities. We argue that this history provides the means to confront contradictions in the neoliberal project, to explore continuities in practice that are effaced and ignored in the dominant paradigm of objective-led teaching, a paradigm that reduces what happens in classrooms to the attainment of pre-specified goals. We conclude with an instance of classroom dialogue that might suggest the continuing need for teachers to be attentive to diversity: to the complexities of culture and history, of language and identity.